Promoting community reintegration using narratives and skills building for young adults with stroke: a protocol for a randomised controlled trial - Lo, Suzanne Hoi Shan (BMC Neurol, 2021)
BACKGROUND: Stroke in adults aged between 18 and 64 years old is increasing significantly worldwide. Studies have reported that this group of young stroke survivors encounters enormous difficulties reintegrating into their social roles. Individualised discussions with healthcare professionals and learning from other survivors are imperative for them to reconstruct their identities after stroke. There is also great demand for community support during their chronic stage of recovery to help them rebuild life skills to promote reintegration. METHODS/DESIGN: This is a randomised controlled trial to investigate the effects of a 24-week Narrative and Skills-building Intervention (NSI) on young stroke survivors’ community reintegration and psychosocial outcomes. A total of 208 adults aged 18–64 years old with a first-ever or recurrent ischaemic or haemorrhagic stroke and have been discharged home will be recruited and randomly assigned to receive usual care or usual care with NSI. The NSI is grounded in Narrative Theory and Bandura’s principles of Self-efficacy and Outcome Expectation, consisting of successive eight individual sessions over six months delivered by a trained facilitator (a registered nurse). Participants will be facilitated to narrate their survival experiences and rebuild core life skills. Videos of peer young stroke survivors’ experiences of recovery will be provided. Outcomes including community reintegration, depressive symptoms, health-related quality of life, self-efficacy, outcome expectation and satisfaction with performance of self-management behaviours will be measured before (T0) and immediately after NSI (T1), then six (T2) and 12 months after NSI (T3). Generalised estimating equations models will be used to compare the differential changes in outcomes across time between the two groups. Focus group interviews will be conducted with the facilitator at T1 and with the participants in the intervention group at T1 and T3. DISCUSSION: This study will evaluate the short and long-term effects of a theory-based NSI on young stroke survivors’ community reintegration and establish a new model of community reintegration after stroke to inform future research. The results will also provide valuable evidence to develop clinical guidelines for young stroke survivors’ community reintegration. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT04560140, registered on 23 September, 2020. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12883-020-02015-5.